Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Honda Vario - Syafrida, Syafrida; Putra, Pandi (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to determine whether the quality of service has an influence on purchasing decisions for Honda Beat motorbikes at PT. Tunas Dwipa Matra Parepare Branch, where the truth is proven, Ha1 is accepted and Ho1 is rejected. and Product Quality has an influence on the Purchase Decision of Honda Vario motorbikes at PT. Tunas Dwipa Matra Branch of Parepare, where the truth is proven, Ha2 is accepted and Ho1 is rejected. As well as Service Quality and Product Quality jointly influence Purchase Decisions. This can be seen from the quality of service and product quality showing the calculated F value = 40.752 with a significance of 0.000 <0.05. So in this study, it can be stated that Service Quality and Product Quality have a joint and significant influence on Purchasing Decisions at PT. Parepare Branch of Dwipa Matra Branch.